Telephone-based depression self-management in Hispanic adults with epilepsy: a pilot randomized controlled trial. Issue 7 (8th May 2021) - Spruill, Tanya M; Friedman, Daniel; Diaz, Laura; Butler, Mark J; Goldfeld, Keith S; O'Kula, Susanna; Montesdeoca, Jacqueline; Payano, Leydi; Shallcross, Amanda J; Kaur, Kiranjot; Tau, Michael; Vazquez, Blanca; et al.
Abstract: Depression is associated with adverse outcomes in epilepsy but is undertreated in this population. Project UPLIFT, a telephone-based depression self-management program, was developed for adults with epilepsy and has been shown to reduce depressive symptoms in English-speaking patients. There remains an unmet need for accessible mental health programs for Hispanic adults with epilepsy. The purpose of this study was to evaluate the feasibility, acceptability, and effects on depressive symptoms of a culturally adapted version of UPLIFT for the Hispanic community. Hispanic patients with elevated depressive symptoms ( n = 72) were enrolled from epilepsy clinics in New York City and randomized to UPLIFT or usual care. UPLIFT was delivered in English or Spanish to small groups in eight weekly telephone sessions. Feasibility was assessed by recruitment, retention, and adherence rates and acceptability was assessed by self-reported satisfaction with the intervention. Depressive symptoms (PHQ-9 scores) were compared between study arms over 12 months. The mean age was 43.3±11.3, 71% of participants were female and 67% were primary Spanish speakers. Recruitment (76% consent rate) and retention rates (86–93%) were high. UPLIFT participants completed a median of six out of eight sessions and satisfaction ratings were high, but rates of long-term practice were low. Rates of clinically significant depressive symptoms (PHQ-9 ≥5) were lower in UPLIFT versus usual care throughout follow-up (63% vs. 72%, 8 weeks; 40% vs. 70%, 6 months; 47% vs. 70%, 12 months). Multivariable-adjusted regressions demonstrated statistically significant differences at 6 months (OR = 0.24, 95% CI, 0.06–0.93), which were slightly reduced at 12 months (OR = 0.30, 95% CI, 0.08–1.16). Results suggest that UPLIFT is feasible and acceptable among Hispanic adults with epilepsy and demonstrate promising effects on depressive symptoms. Larger trials in geographically diverse samples are warranted.